THE GENUS LASIANTHUS (RUBIACEAE) IN WAWONII ISLAND, SOUTHEAST SULAWESI, INDONESIA - T.Rugayah Rugayah; Siti Sunarti (BRIN Publishing (Penerbit BRIN), 2017)
RUGAYAH & SUNARTI, S. 2017. The genus Lasianthus (Rubiaceae) in Wawonii Island, Sountheast Sulawesi, Indonesia. Reinwardtia 16 (2): 97–101. — Recent botanical excursions carried out at Wawonii island, Southeast Sula-wesi yielded two Lasianthus novelties distinct from other Lasianthus species enumerated for Sulawesi. These two new species are described here as Lasianthus wawoniiensis Rugayah & Sunarti and L. macrobracteatus Rugayah & Sunarti. Descriptions and illustrations of the two new species are provided, including an identification key to all Lasianthus species occurring in the area.